2013
DOI: 10.5007/2175-7925.2013v26n3p139
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre variáveis ambientais e a estrutura da comunidade de peixes em córregos das bacias do Rio das Mortes e do rio Xingu – MT, Brasil

Abstract: As variáveis ambientais podem determinar e estruturar a composição da fauna de peixes. Estudos que comparem diferenças entre variáveis físicas e químicas da água entre bacias hidrográficas próximas são escassos. Este artigo teve por objetivo verificar quais variáveis limnológicas estão relacionadas à distribuição das espécies de peixes em duas bacias hidrográficas. Para tanto, foram amostrados 20 córregos, divididos entre as bacias do Rio das Mortes e do rio Xingu. Em cada ponto foram medidos um total de 8 var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The average stream fish species richness observed in our study streams was 15 species, like the value found in other stream fish studies in this ecoregion (Melo et al 2004, Matos et al 2013, Barbosa et al 2019, Oliveira et al 2020). However, our data showed a wide variance in the number of species per stream.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The average stream fish species richness observed in our study streams was 15 species, like the value found in other stream fish studies in this ecoregion (Melo et al 2004, Matos et al 2013, Barbosa et al 2019, Oliveira et al 2020). However, our data showed a wide variance in the number of species per stream.…”
Section: Discussionsupporting
confidence: 88%
“…Considering the high fish species endemicity within these basins, there is a significant likelihood that many of these species identified only up to the genera level are new species. Previous studies on stream fish in these basins have also found similar patterns, with a great number of species not yet described ( Melo et al 2004, Matos et al 2013, Jarduli et al 2014, Oliveira et al 2020. This large number of species to be described is one of the most important knowledge gaps in biodiversity (Linnean shortfalls) that needs to be addressed (Hortal et al 2015).…”
Section: Discussionmentioning
confidence: 65%
“…The result of the many characteristics of habitats, which influence the patterns of composition and diversity of fish communities, such as environmental filters, the availability of resources, and the complexity of habitats (Felipe and Súarez, 2010), are aspects that contribute to installation and development of fish species. Araújo and Tejerina-Garro (2009) and Matos et al (2013) showed that the structuring and distribution of the fish community may be more associated with the physical and structural characteristics of the environment, favouring the occurrence of species; however, when these are destroyed or altered, more sensitive fish species can be removed locally, contributing to the installation of more tolerant species.…”
Section: Discussionmentioning
confidence: 99%
“…Our results highlight the importance of preservation of the integrity of headwaters ecosystems. However, the rapid environmental change observed in this region for agriculture or livestock has affected the water quality of the streams , Matos et al 2013. Furthermore, this represents a threat to the biodiversity of this ecoregion putting many species at risk of disappearing before they are described.…”
Section: Resultsmentioning
confidence: 99%